Differences in myocardial involvement between new onset and longstanding systemic lupus erythematosus patients assessed by cardiovascular magnetic resonance - Zhen Wang; Xing Tang; Chaohui Hang; Hui Gao; Jinxiu Yang; Yuchi Han; Yongqiang Yu; Zongwen Shuai; Ren Zhao; Xiaohu Li (European Journal of Radiology Open, 2025)
Objectives: Subclinical myocardial involvement is common in systemic lupus erythematosus (SLE), but differences between new onset and longstanding SLE are not fully elucidated. This study compared myocardial involvement in new onset versus longstanding SLE using cardiovascular magnetic resonance (CMR). Materials and methods: We prospectively enrolled 24 drug-naïve new onset SLE patients, 27 longstanding SLE patients, and 20 healthy controls. All participants underwent clinical evaluation and CMR examination. We analyzed left ventricular (LV) morphological, functional parameters, and tissue characterization parameters: native T1, T2, extracellular volume fraction (ECV), and late gadolinium enhancement (LGE). Results: Both new onset and longstanding SLE groups showed elevated native T1, T2, and ECV values compared to the control group (all P < 0.05). Additionally, the new onset SLE group exhibited higher T2 values compared to the longstanding SLE group [55.3 vs. 52.8 ms, P < 0.05]. The new onset group also demonstrated higher left ventricular (LV) end-diastolic volume index (LVEDVi), LV end-systolic volume index (LVSVi), and LV mass index (LVMi) than controls (all P < 0.05), with LVEDVi significantly higher than in the longstanding group (P < 0.05). Conclusion: CMR tissue characterization imaging can detect early myocardial involvement in patients with new onset and longstanding SLE. Patients with new onset SLE exhibit more pronounced myocardial edema than those with longstanding SLE. This suggests that SLE patients are at risk of myocardial damage at various stages of the disease, underscoring the need for early monitoring and long-term management to prevent the progression of myocardial remodeling.